EXPLORATION OF SHARPENING FOOTBALL DRIBBLING TECHNIQUE SKILLS BY APPLYING THE TEACHING GAMES FOR UNDERSTANDING (TGFU) APPROACH STRATEGY: A REVIEW STUDY - Leni Apriani; Doni, Rama (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
Dribbling is one of the skills base in football holding​ role important in success games. However, learning dribbling techniques often face​ challenge in matter effectiveness and engagement Players. Approach Teaching Games for Understanding (TGFU) is a learning strategy that emphasizes understanding tactical and taking decision through modified game so that can increase dribbling skills in more effective. This study aiming for explore effectiveness implementation of TGFU strategy in hone skills soccer dribbling techniques based on study literature latest. The method used in study This is review study with analyze various literature that discusses implementation of TGFU in learning skills base football. Study results show that TGFU approach is capable increase dribbling skills through experience play more​ contextual, improvement understanding tactical, as well as involvement active player in learning. In addition, this strategy also provides benefit in matter motivation, creativity, and decision making more decisions​ good in the field. With Thus, the TGFU approach can be used as an effective alternative strategy in learning soccer dribbling skills.